International Conference Fluid Power 2025: Conference Proceedings (University of Maribor Press, 2025)
The International Fluid Power Conferences are a two day event, intended for all those professionally-involved with hydraulic or pneumatic power devices and for all those, wishing to be informed about the ‘state of the art’, new findings and innovations within the field of hydraulics and pneumatics. All papers included in the conference program are reviewed and collected in the conference proceedings. The gathering of experts at this conference in Maribor has been a tradition since 1995, and is organised by the Faculty of Mechanical Engineering at the University of Maribor, in Slovenia. Fluid Power conferences are organised every second year and cover those principal technical events within the field of fluid power technologies in Slovenia, and throughout this region of Europe. This year’s conference FT2025 is taking place on the 17th and 18th September in Maribor, at Congress centre Habakuk.